Potensi Jamur Entomopatogen Untuk Mengendalikan Hama Ulat Grayak (Spodoptera litura) Fabricius (Lepidoptera : Noctuidae) Pada Tanaman Tembakau di Rumah Kasa - Irna Masyitah; Suzanna Fitriany Sitepu; Irda Safni (Universitas Sumatera Utara, 2017)
Spodoptera litura is an important pest for tobacco. The objective of this study was to determine the potency of entomopathogenic fungi at various conidia density against Spodoptera litura on tobacco. This study was conducted in screen house, Faculty of Agriculture, University of Sumatera Utara from October until February 2016. This study was used a randomized block design (RBD) with two factors and three replications. The first factor was the conidia density (106, 107, 108 conidia/ml), the second factor was the type of fungi (Metarhizium anisopliae, Beauveria bassiana, and Lecanicillium lecanii) The result showed that: the highest larval mortality was at concentration of 108 conidia/ml (73.33%). The highest larval mortality was on M. anisopliae (57.78%) followed by B. bassiana (51.11%) and L. lecanii (40.00%). The infected larvae showed slow movements, color changes to paleness, decreased appitite, over time silent and die. The dead larva body hardened and blackened. The highest intensity of fungal infection was at concentration of 106 conidia/ml (42.22%).